The Role of the Holy Qur'an in Shaping and Building Human Behaviour (AComprehensive Social Study): Peran Al-Qur'an dalam Membentuk dan Membangun Perilaku Manusia (Studi Sosial Komprehensif) - Zaman Sahib Darwish Al-Mohanna (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The Holy Qur’an serves as a fundamental source of moral values, ethics, and social guidance in Islamic societies. Specific Background: In Iraq, characterized by sectarian diversity and strong religious traditions, Qur’anic teachings contribute to shaping individual and collective behaviour. Knowledge Gap: However, integrated social analyses examining how Qur’anic principles guide behavioural formation within the Iraqi context remain limited. Aims: This study aims to analyse the role of the Holy Qur’an in shaping human behaviour in Iraqi society from a social perspective. Results: The findings indicate that the Qur’an provides a behavioural framework through legislative guidance, Qur’anic narratives, moral accountability, and ethical values such as justice, responsibility, cooperation, and spiritual purification. The study also shows that religious authorities, educational institutions, and community initiatives contribute to translating Qur’anic teachings into social practices. Novelty: This research presents an integrated social analysis linking Qur’anic teachings, interpretative diversity between Sunni and Shia traditions, and behavioural formation in Iraq. Implications: Strengthening Qur’anic education and encouraging inter-sectarian dialogue may support the development of ethical conduct and social cohesion in Iraqi society. Highlights• Qur’anic teachings provide a comprehensive ethical system guiding personal and social conduct in Iraq• Religious authorities and institutions contribute to translating scriptural teachings into community practices• Sectarian interpretative diversity shapes the understanding of moral values in Iraqi society KeywordsQur’anic Values; Human Behaviour; Iraqi Society; Social Ethics; Islamic Teachings